2019
DOI: 10.1039/c9ra07965c
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of bladder acellular matrix cross-linked by dialdehyde carboxymethyl cellulose for bladder tissue engineering

Abstract: To address the disadvantage of rapid degradation and serious immune response of bladder acellular matrix tissues in clinical application, oxidized carboxymethyl cellulose was developed to replace commonly used glutaraldehyde, to fix BAM tissues for lower cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Until now, many scientists have tried to develop suitable biodegradable materials for urethral reconstructions. A few kinds of natural matrices, including bladder acellular matrix (BAM) [ 140 , 141 ] and small intestinal submucosa (SIS) [ 142 , 143 ], as well as popular synthetic polymeric materials were used to treat urethra stricture in preclinical or clinical stages. It has been reported that the BAM and SIS from other species or individuals may present a potential risk of disease transmission, and the acidic degradation products from most synthetic polymer probably have some negative effect for cell growth and immune response.…”
Section: Advanced Biomedical Applications Of Rsf Materialsmentioning
confidence: 99%
“…Until now, many scientists have tried to develop suitable biodegradable materials for urethral reconstructions. A few kinds of natural matrices, including bladder acellular matrix (BAM) [ 140 , 141 ] and small intestinal submucosa (SIS) [ 142 , 143 ], as well as popular synthetic polymeric materials were used to treat urethra stricture in preclinical or clinical stages. It has been reported that the BAM and SIS from other species or individuals may present a potential risk of disease transmission, and the acidic degradation products from most synthetic polymer probably have some negative effect for cell growth and immune response.…”
Section: Advanced Biomedical Applications Of Rsf Materialsmentioning
confidence: 99%
“…[ 118 ] Current existing methods for eliminating acellular antigenicity include genetic modification [ 119–128 ] and fixation. [ 94,105,129–137 ]…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%
“…DCMC was evaluated and proved to be feasible for crosslinking bladder acellular matrix. [ 129 ] DCMC‐fixed bladder was stable with maintained tissue ultrastructure reduced α ‐Gal expression and preserved functional growth factors. Chondroitin sulfate‐crosslinked decellularized goat corneas elicited lower immune responses than non‐crosslinked decellularized corneas due to the restoration of distorted collagen fibril conformation.…”
Section: Immunocompatibility Of Engineered Tissue or Organ‐based Implantsmentioning
confidence: 99%
“…In contrast, the anionic carboxymethylcellulose (CMC) is commonly used as a solvent or excipient for drug formulations injected into bladder for disease treatments. , Use for development of a drug-delivery system in bladder, however, has been rare, although there were studies reporting the mucoadhesive properties in bladder. The developed silver nanoparticle containing a carboxymethylcellulose hydrogel composite exhibited high antibacterial activity when tested against a variety of urinary tract infection pathogens . Oxidized carboxymethylcellulose was used as a cross-linking agent replacement to reduce the cytotoxicity and immune response generated by glutaraldehyde in bladder acellular matrix in addition to slowing down the deterioration rate . Incidentally, carboxymethylcellulose application has reported enhanced tumor inhibition exceeding that of pristine drugs, extended systemic circulation, and reduced toxicity. …”
Section: Introductionmentioning
confidence: 99%
“…22 Oxidized carboxymethylcellulose was used as a cross-linking agent replacement to reduce the cytotoxicity and immune response generated by glutaraldehyde in bladder acellular matrix in addition to slowing down the deterioration rate. 23 Incidentally, carboxymethylcellulose application has reported enhanced tumor inhibition exceeding that of pristine drugs, extended systemic circulation, and reduced toxicity. 24−26 Graphene oxide (GO) is a two-dimensional (2-D) material that has been brought into the limelight in recent years due to its coveted properties in the biomedical field.…”
Section: ■ Introductionmentioning
confidence: 99%